Global trends in using digital technology and smart inhalers in asthma management, problems, challenges and future directions - Bataduwaarachchi, Vipula R.; Gunasekara, Amandi I.; Cruz, Leon G. D. (International Journal of Basic & Clinical Pharmacology, 2025)
Asthma management is increasingly patient-centred and tailored to individual needs. Medication non-adherence and a shortage of skilled personnel continue to pose challenges in asthma care. Digital health solutions and smart inhalers have shown promise in addressing these issues; however, they have not been assessed by meta-analysis. This systematic review and meta-analysis assess the effectiveness of using digital technology and smart inhalers in asthma care, exploring challenges and future directions in depth. We followed the preferred reporting items for systematic reviews and meta-analyses. The selected outcomes, compliance with asthma management and the level of asthma control were assessed separately. The results were displayed using a Forest plot and tables. Our data demonstrate significant effectiveness in achieving compliance and asthma control with digital health and smart inhaler interventions compared with controls. The pooled odds ratio for compliance was 2.64 (95% CI: 1.49-4.68); digital health and smart inhaler interventions have been shown to improve compliance significantly. However, its use is significantly limited, and differences are observed. Factors affecting these are further discussed with possible solutions. Based on the controlled trials, digital health and smart inhalers can revolutionize asthma care. To overcome current challenges, close collaboration between healthcare and technology teams is necessary, with implementation targeted to select groups and cost-effective. Although the initial investment is substantial, the long-term cost-effectiveness of digital applications in asthma care is likely to be favourable.